Adolescentes em conflito com a lei ao ingresso no Sistema Socioeducativo no município de Fortaleza: perfil epidemiológico e de saúde - Nogueira, Eliana Rodrigues Freitas (2019)
The Unified Health System (SUS) provides that the health promotion of adolescents in conflict with the law must have an educational, comprehensive, humanized and quality bias. Health care in socio-educational measures is part of Primary Care, which provides for prevention actions and specific mental health care, alcohol and drug use, sexual and reproductive health, health of adolescents with disabilities and violence. This service also includes health promotion actions, which encourage autonomy and the development of skills to improve interpersonal relationships. Adolescence comprises a period of great vulnerability to sexually transmitted infections, as many adolescents begin sexual life when they still have little knowledge, having a mistaken view of the personal risk of acquiring them. Adolescents in conflict with the law find themselves in an environment of overcrowding, precarious physical space and exposure to the risks of diseases and practices of violence. In view of this problem, the present study aimed to characterize and describe the epidemiological profile and the health scenario of adolescents in compliance with socio-educational measures in the state of Ceará. This was an epidemiological, descriptive, cross-sectional study with municipal coverage. The collection took place between the months of September and November 2018, at the Luis Barros Montenegro Reception Unit, Fortaleza, Ceará. This study aimed to promote the health of the confined population and contribute to the control and / or reduction of the most frequent diseases that affect health, and to establish among its priorities the implementation of actions for health prevention. We conclude that intervening in adolescents in compliance with the socio-educational measure goes far beyond just offering opportunities in the period that they are in a socio-educational unit. It is an intersectoral and interinstitutional work, because in addition to the adolescent's family who must be part of all socio-education, he must be the protagonist of the policy to which he is inserted. Policies must be interlinked so that we can have concrete and continuous results.